Hair Growth-Promoting Effects of Lavender Oil in C57BL/6 Mice - Lee, Boo Hyeong (Toxicol Res, 2016)
The purpose of this study was to determine the hair growth effects of lavender oil (LO) in female C57BL/6 mice. The experimental animals were divided into a normal group (N: saline), a vehicle control group (VC: jojoba oil), a positive control group (PC: 3% minoxidil), experimental group 1 (E1: 3% LO), and experimental group 2 (E2: 5% LO). Test compound solutions were topically applied to the backs of the mice (100 μL per application), once per day, 5 times a week, for 4 weeks. The changes in hair follicle number, dermal thickness, and hair follicle depth were observed in skin tissues stained with hematoxylin and eosin, and the number of mast cells was measured in the dermal and hypodermal layers stained with toluidine blue. PC, E1, and E2 groups showed a significantly increased number of hair follicles, deepened hair follicle depth, and thickened dermal layer, along with a significantly decreased number of mast cells compared to the N group. These results indicated that LO has a marked hair growth-promoting effect, as observed morphologically and histologically. There was no significant difference in the weight of the thymus among the groups. However, both absolute and relative weights of the spleen were significantly higher in the PC group than in the N, VC, E1, or E2 group at week 4. Thus, LO could be practically applied as a hair growth-promoting agent.